Pengaruh Disiplin dan Keselamatan, Kesehatan Kerja terhadap Kinerja Karyawan Pt Mutiara Medical Service di Kalimantan Tengah - Idamanwati Hia; Harries Madiistriyatno; Dudun Junaedi (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2026)
This study aims to analyze the influence of work discipline and occupational safety and health (OSH) on employee performance at PT Mutiara Medical Service in Central Kalimantan. The study is motivated by the growing importance of maintaining high levels of discipline and ensuring a safe and healthy work environment to improve employee productivity and organizational performance. A quantitative research design was employed using descriptive and verification approaches to examine the relationships among the variables. Data were collected through structured questionnaires distributed to 66 employees of PT Mutiara Medical Service in Central Kalimantan. The collected data were analyzed using multiple linear regression to determine both the individual and combined effects of work discipline and occupational safety and health on employee performance. The findings reveal that work discipline has a positive and significant effect on employee performance. Likewise, occupational safety and health also demonstrate a positive and significant influence on employee performance. Furthermore, the simultaneous analysis confirms that both variables jointly contribute significantly to improving employee performance. These results suggest that organizations should strengthen the implementation of disciplinary policies and continuously improve occupational safety and health programs to create a productive work environment. Such efforts are expected to enhance employee performance, support organizational effectiveness, and contribute to the long-term sustainability of the company.